Journeys Home Research Report No. 2: Findings from Waves 1 and 2 - Chigavazira, A; Johnson, G; Moschion, J; Scutella, R; Wooden, M; Tseng, Y (My University, 2013)
This Research Report presents key findings from the first two waves of the JH study, which were conducted over the periods September to November 2011 and March to May 2012 respectively. The research questions guiding our analysis include: • How persistent / episodic is homelessness? • What factors are associated with instability/stability in housing? • What characteristics distinguish at-risk households including families that become homeless from those that do not? • What are the protective factors for staying out of homelessness? • What are the triggers that lead to homelessness? • What factors are important in the road out of homelessness? To gain some insight into these issues we examine JH respondents’ transitions in to and out of homelessness between waves 1 and 2 of the study. As JH is still in its early stages, the analysis presented is purely descriptive as we are interested in ascertaining whether there is any early evidence to suggest whether any particular risk or protective factors are associated with certain homeless transitions.
Journeys Home Research Reports
Keywords: Housing; Life Events -- Resilience and Adversity; Disadvantage; Disadvantage, adversity and resilience; Disadvantage; Life Events; Housing; Resilience and Adversity; Dsiadvantage, adversity and resilience; Adversity and resilience